Football in the capital: a local study with national consequences. (3rd April 2019) - Curry, Graham
Abstract : By the late 1850s, clubs were formed in England with the sole purpose of playing football. Many began in the London area where, in the autumn of 1863 the Football Association held its first meetings. The people behind the capital's upsurge of interest came mainly from the four major public schools in and around London – Eton, Westminster, Harrow and Charterhouse – and former pupils of these institutions were prominent in establishing the local subculture. It is suggested in this article that the members of these early London clubs were the architects of the form of the game which became known as Association Football, an amalgam of the varieties being played at the aforementioned London public schools. The adherents to other forms which had existed in different parts of the country eventually discarded their cherished versions in favour of what had become, in short, a public school-inspired modern sport-form.